Intersexuality and the law : why sex matters - Greenberg, Julie A. (New York : New York University Press, 2016)
This term 'intersex' evokes diverse images, typically of people who are both male and female or neither male nor female. Neither vision is accurate. In this work, Greenberg examines the role that legal institutions can play in portecting the rights of people with an intersex condition.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Intersex people -- Legal status, laws, etc. -- United States; Intersex people -- United States -- Social conditions; Law; United States of America, USA; Gender studies, gender groups; Law & society, gender issues; Family law